Designing Vaccines for the Twenty-First Century Society - Finco, Oretta; Rappuoli, Rino (Frontiers in Immunology, 2014)
The history of vaccination clearly demonstrates that vaccines have been highly successful in preventing infectious diseases, reducing significantly the incidence of childhood diseases and mortality. However many infections are still not preventable with the currently available vaccines and they represent a major cause of mortality worldwide. In the 21st century, the innovation brought by novel technologies in antigen discovery and formulation together with a deeper knowledge of the human immune responses are paving the way for the development of new vaccines. Final goal will be to rationally design effective vaccines where conventional approaches have failed.